Coral growth rates from the Holocene Canada Honda fossil reef, Southwestern Dominican Republic: Comparisons with modern counterparts in high sedimentation settings - Cuevas, D. N.; Sherman, C. E.; Ramírez, W.; Hubbard, D. K. (Caribbean Journal of Science, 2009)
The Holocene Canada Honda fossil reef, located in southwestern Dominican Republic, provides a unique opportunity to examine a well-preserved fossil coral reef that thrived in a high-sedimentation environment between 9,000 to 5,000 years ago. Measurements of coral growth rates from the corals Montastraea faveolata and Siderastrea siderea were conducted and comparisons made with growth rate data of these same species from modern coral reefs throughout the Caribbean. Also, assessments of coral species abundance, morphology, age, and distribution, as well as reef sediment composition, were made to determine the paleoenvironment of reef accretion. This reef is characterized by a high relative abundance of sediment-tolerant coral species that have a tendency to form almost monospecific stands. Individual colonies have a propensity to grow as encrusting, dome-shaped, platy-like forms and specimens of Montastraea faveolata commonly contain bands of sediment incorporated into the skeleton. Calibrated radiocarbon ages of fossil corals range from 9,256 +/- 137 to 6,737 +/- 94.5 BP. Correlation of radiocarbon ages with well-established Holocene sea-level curves indicates that most corals on this reef developed at depths >15m. Measured growth rates in Siderastrea siderea (0.2-0.4 cm/yr) and Montastraea faveolata (0.09-0.44 cm/yr) are relatively low compared with growth rates from modern reef sites, indicating reduced light intensity caused by coral growth at depths greater than 15 m. Reef sediment is characterized by more than 85% carbonate material. A significant portion of the carbonate is allochtonous and was derived from nearby Neogene limestones. The reef was able to survive under high-sedimentation conditions because the high carbonate content of incoming terrigenous sediment would have allowed better light penetration and probable sporadic storms would provide intervening low-sedimentation periods during which reef corals could respond and grow back, keeping-up with sedimentation.
695voTimes Cited:0 Cited References Count:47
Keywords: australia; Belize; Caribbean; community; degradation; enriquillo valley; florida; great-barrier-reef; linear extension; montastraea-annularis; paluma shoals; record; siltation stress; skeletal extension; turbidity

Age and origin of Late Quaternary eolianite, Kaiehu Point (Moomomi), Molokai, Hawaii - Fletcher, C. H.; Murray-Wallace, C. V.; Glenn, C. R.; Sherman, C. E.; Popp, B.; Hessler, A. (Journal of Coastal Research, 2005)
A well-preserved, vertically stacked succession of two genetically distinct eolianites and associated caliche paleosol units, capped by modern and Holocene coastal dunes, occurs at Kaiehu Point, west Molokai, Hawaii. The Pleistocene eolianite facies comprise well-cemented, medium grained skeletal carbonate sand and their morphostratigraphic context implies formation at times of lower than present sea level. Amino acid racernization (AAR) evidence suggests eolianite formation late in marine Oxygen Isotope Stage (OIS) 5, but lacks the precision to uniquely define in which isotopic substage the deposits formed. Coupled with the AAR results, the morphostratigraphic evidence, would suggest that the Lower Eolianite formed in OIS 5c and the Middle Eolianite during 5a with their superposed caliche paleosols having formed in subsequent stadial stages. The unconsolidated coastal sand dunes of Holocene age contain reworked Late Pleistocene skeletal carbonate sand based on AAR evidence. The most likely source of the reworked carbonate is from the erosion of the eolianites at Kaiehu Point. The Pleistocene eolianite-caliche paleosol sediments reveal variable Mg-content, stable isotope ratios and petrological characteristics consistent with changing degrees of weathering intensity and meteoric diagenesis. These changes are attributed to orographic effects resulting from relative sea-level changes. Accordingly, a two-phase model is favored for the formation of the eolianite-paleosol successions at Kaiehu Point, west Molokai. Eolianite sedimentation is initiated at times of marginally lower sea levels promoting the landward migration of bioclastic sand to form extensive eolian sandsheets. This is followed by a more pronounced phase of pedogenesis associated with a further fall in sea level and concomitant increased rainfall due to enhanced orographic effects.
Sp. Iss. 42947fu Times Cited:3 Cited References Count:50
Keywords: Amino acid racemization; aminostratigraphy; bermuda; carbonate lithofacies; cementation; cliche paleosols; eolianite; hawaii; island; Late Quaternary; limestone petrology; Marine; molokai; oahu; precipitation; sea level; sea-level; south-australia; Stable isotopes; stratigraphy

Marine and meteoric diagenesis of pleistocene carbonates from a nearshore submarine terrace, Ohau, Hawaii - Sherman, C. E.; Fletcher, C. H.; Rubin, K. H. (Journal of Sedimentary Research, 1999)
id: 298

Marine and meteoric diagenesis of Pleistocene carbonates from a nearshore submarine terrace, Oahu, Hawaii - Sherman, C. E.; Fletcher, C. H.; Rubin, K. H. (Journal of Sedimentary Research, 1999)
The nearshore slope of Oahu consists of a shallowly dipping shelf extending from the shoreline out to the similar to -20 m contour, where there is a sharp break in slope down to similar to -30 m, Limestones recovered in a series of short cores taken from this nearshore terrace are typical of shallow-marine reef environments and comprise either a branching-coral or massive-coral facies, The composition as well as shoreward zonation of facies suggests that the terrace represents an in situ fossil reef complex. Th-U ages of in situ corals are all Pleistocene and suggest that the bulk of the feature formed during marine oxygen isotope stage 7. Later accretion along the seaward front of the terrace occurred during marine oxygen isotope substages 5a and/or 5c. Deposition during these interglacial highstands has not previously been documented in the sea-level record on Oahu,Although the diagenetic record in the cored samples is incomplete, three periods of diagenesis are identified: early shallow marine, meteoric, and post-meteoric shallow marine. Early shallow-marine diagenesis includes cementation by aragonite and Mg calcite in an active marine phreatic zone and predominantly micritization in a stagnant marine phreatic zone. Meteoric processes occurred in the vadose zone and include precipitation of calcite (needle fibers, meniscus cements, micritic networks), neomorphism, and dissolution. All limestones are now in an active marine phreatic zone. Evidence of post-meteoric shallow-marine diagenesis is found in last-generation Mg calcite cements and internal sediments occurring directly on limestone substrates that have otherwise been stabilized to calcite. The present seafloor is undergoing extensive biological and physical erosion. No Holocene limestones were recovered. Petrographic and geochemical signatures of subaerial exposure and meteoric diagenesis are recognized within the upper several centimeters of all cores. Thus, the present seafloor in the study area is a flooded Pleistocene subaerial exposure surface.
A237cq Times Cited:42 Cited References Count:79
Keywords: barrier-reef; calcite; corals; fringing-reef; Holocene; oxygen isotopes; platform; recrystallization; sea-level; stabilization